The Relationship between Macro Nutrient Intake and the Adequacy and Nutritional Status of Santri at Pondok Tahfidz Wadil Quran, South Tangerang - Helda Khusun; Hanifa Febriyanti; Yuli Dwi Setyowati; Widya Asih Lestari (Ikatan Sarjana Gizi Indonesia (ISAGI), 2025)
Nutritional problems among Islamic boarding school students need more attention, because the quality of food served at the boarding school is not widely known and tends to have a monotonous menu. On the other hand, Islamic boarding school students are known to often have the habit of consuming snack foods. The purpose of this study was to determine the relationship between the intake of macronutrients in foods provided by the boarding schools and snacks bought by the stidents with the adequacy and nutritional status of students at the Tahfidz Wadil Qur'an Islamic Boarding School in South Tangerang. This study was a cross-Sectional study with collecting data from all students fulfilling the inclusion criteria (n=67). Data analysis used the Spearman Rank correlation test. Research. The study showed that around 14-28% of macronutrient requirements was fulfilled from snacks bought by the students, instead of food provided by the boarding school.There is a relationship between the intake of macronutrients (energy, protein, fat, and carbohydrates) in main foods and nutritional adequacy. There is a relationship between the intake of macronutrients (energy, protein, fat, and carbohydrates) in snack foods and nutritional adequacy. There is no relationship between the intake of macronutrients (energy, protein, fat, and carbohydrates) in main foods and status. There is no relationship between the intake of macronutrients (energy, protein, and carbohydrates) in snack foods and nutritional status. Research suggestion: For Islamic boarding schools Conducting routine monitoring of the nutritional status of students, and paying more attention to the variety of foods that will be given to students.